East and Central European students’ financial self-sufficiency during their university years - Hvozdetska, B.; Varha, N.; Kocsis, Zs.; Nechitailo, I. S.; Нечітайло, І. С.; Bartosh, O. (Corvinus journal of sociology and social policy. – 2022. – Vol. 13, № 2. – P. 53-78, 2022)
Identifying the problems of youth requires taking into account the transformational processes that affect individuals’ development, the formation of a certain social environment, and changing youth market orientation priorities. The current orientations of youth – inflated expectations, aspirations for a quality education, employment, higher-status achievement, improved financial status, etc. – contradict the reality that in fact involves limited access to social status and professional realization, thereby creating barriers to fulfilment. The novelty of this research is that we evaluate the literature and empirical data and examine the self-sufficiency of university students in post-socialist countries as a factor in their adulthood and an indicator of life readiness according to the principles of a democratic society and rules of the market economy. The study aims to determine the role of economic factors in the process of obtaining a higher education for students in Central and Eastern Europe (Hungary, Slovakia, Romania, Serbia, and Ukraine) through an analysis of students’ financial self-sufficiency during their university years. The presented research results demonstrate students’ financial selfsufficiency during their university studies and the proportion of students’ average monthly expenses in relation to income. The comparative analysis confirms that the respondents’ financial situation in the five countries under study is almost identical.

Виявлення проблем молоді потребує врахування трансформаційних процесів, що впливають на розвиток особистості, формування певного соціального середовища, зміну пріоритетів молодіжної ринкової орієнтації. Сучасні орієнтації молоді – завищені очікування, прагнення до якісної освіти, працевлаштування, досягнення вищого статусу, покращення матеріального становища тощо – суперечать реальності, яка фактично передбачає обмежений доступ до соціального статусу та професійної реалізації, створюючи тим самим бар’єри для самореалізації. Новизна цього дослідження полягає в тому, що ми оцінюємо літературні та емпіричні дані та досліджуємо самодостатність студентів вищих навчальних закладів постсоціалістичних країн як фактор їхньої дорослості та показник готовності до життя за принципами демократичного суспільства та правилами ринкової економіки. Метою дослідження є визначення ролі економічних факторів у процесі здобуття вищої освіти студентами в країнах Центральної та Східної Європи (Угорщина, Словаччина, Румунія, Сербія та Україна) через аналіз фінансової самозабезпеченості студентів під час навчання в університеті. Представлені результати дослідження демонструють фінансову самозабезпеченість студентів під час навчання у зво та співвідношення середньомісячних витрат студентів до доходів. Порівняльний аналіз підтверджує, що матеріальне становище респондентів у п’яти досліджуваних країнах майже однакове.

Выявление проблем молодежи требует учета трансформационных процессов, влияющих на развитие личности, формирование определенной социальной среды, изменение приоритетов молодежной рыночной ориентации. Современные ориентации молодежи – завышенные ожидания, стремление к качественному образованию, трудоустройству, достижению высшего статуса, улучшению материального положения и т.п. – противоречат реальности, которая фактически предполагает ограниченный доступ к социальному статусу и профессиональной реализации, создавая тем самым барьеры для самореализации. Новизна этого исследования заключается в том, что мы оцениваем литературные и эмпирические данные и исследуем самодостаточность студентов высших учебных заведений постсоциалистических стран как фактор взрослости и показатель готовности к жизни по принципам демократического общества и правилам рыночной экономики. Целью исследования является определение роли экономических факторов в процессе получения высшего образования студентами в странах Центральной и Восточной Европы (Венгрия, Словакия, Румыния, Сербия и Украина) путем анализа финансовой самообеспеченности студентов во время обучения в университете. Представленные результаты исследования демонстрируют финансовую самообеспеченность студентов при обучении и соотношение среднемесячных расходов студентов к доходам. Сравнительный анализ подтверждает, что материальное положение респондентов в пяти изучаемых странах почти одинаково.
Keywords: publikatsii u WoS; Ukraine; youth; students’ financial self-sufficiency; life orientations; adulthood; democracy; market relations; post-socialist countries; Hungary; Slovakia; Romania; Serbia; Україна; молодь; фінансова самозабезпеченість студентів; життєві орієнтації; дорослість; демократія; ринкові відносини; постсоціалістичні країни